Proceedings of the First International Conference on Progressive Civil Society (ICONPROCS 2019) 2019
DOI: 10.2991/iconprocs-19.2019.25
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Job Satisfaction on Employee Work Productivity

Abstract: Job satisfaction has a role of influencing work productivity. This study aims to empirically examine the role of job satisfaction on employee work productivity at the University of X Yogyakarta. The research sample is permanent and active employees who have worked for at least one year. The selection of research samples is done through randomization, with a simple random sampling technique. Methods of data collection are done by using the scale of work productivity and job satisfaction scale. Data analysis use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…The relationship between employee productivity and job satisfaction is JOCM 36,6 bidirectional, as some scholars contend that satisfaction leads to productivity, whereas others argue that productivity precedes satisfaction (Deepa et al, 2014;Mamiseishvili and Rosser, 2011). In a recent study conducted among faculty members in Indonesia, researchers found that productivity is positively associated with job satisfaction (Tentama et al, 2019). In light of available empirical evidence, we offer the following hypothesis:…”
Section: Employee Productivity and Job Satisfactionmentioning
confidence: 87%
“…The relationship between employee productivity and job satisfaction is JOCM 36,6 bidirectional, as some scholars contend that satisfaction leads to productivity, whereas others argue that productivity precedes satisfaction (Deepa et al, 2014;Mamiseishvili and Rosser, 2011). In a recent study conducted among faculty members in Indonesia, researchers found that productivity is positively associated with job satisfaction (Tentama et al, 2019). In light of available empirical evidence, we offer the following hypothesis:…”
Section: Employee Productivity and Job Satisfactionmentioning
confidence: 87%
“…Make a decision on hiring personnel; in this approach, the ratio of price and quality is always considered before. The employer analyses how much the employee costs and what he can give the organization [14]. Talented employees are a symbol of success for any company.…”
Section: Effective Methodsmentioning
confidence: 99%
“…These factors are also called hygienic or dissatisfaction and are mainly related to the work environment, including organizational policy and administration; interpersonal relationships with supervisors, co-workers; working conditions; salary; supervision; status; and work security (Herzberg, 1965). If the organization can create a comfortable work situation, a suitable salary and always maintain relationships between coworkers, then employees will have high job satisfaction (Tentama et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%